Multi-Tasking POM Systems - Sullivan, Kevin P.; Yin, Qiushi; Collins-Wildman, Daniel L.; Tao, Meilin; Geletii, Yurii V.; Musaev, Djamaladdin G.; Lian, Tianquan; Hill, Craig L. (Frontiers in Chemistry, 2018)
Polyoxometalate (POM)-based materials of current interest are summarized, and specific types of POM-containing systems are described in which material facilitates multiple complex interactions or catalytic processes. We specifically highlight POM-containing multi-hydrogen-bonding polymers that form gels upon exposure to select organic liquids and simultaneously catalyze hydrolytic or oxidative decontamination, as well as water oxidation catalysts (WOCs) that can be interfaced with light-absorbing photoelectrode materials for photoelectrocatalytic water splitting.